Genesis system - Brand?o, Rodrigo Carneiro (2012)
This work discusses the main concepts and features of an Internet of Services, concept in which ?everything is seen as a service?. Also discusses some proposals for future network centric-services and mixed kernel, centered on hosts, services and content. Based on these studies, we propose the Genesis System, a conceptual architecture characterized by loose coupling, reusability and composition of services. Its main benefit refers to the intrinsic flexibility of the added services that can be orchestrated at runtime view of a flexible, appropriate and satisfying the needs of specific business processes, complex and dynamic.